Synthesis of cobalt doped iron oxide for pollutants degradation under sunlight - Abdul Rashid, Jannatul Ma’wa; Mohammad Repin, Nur Azmina; Che Mat, Ahmad Nazeer; Yaafar, Mohd Rabani; Taib, Nurul Izza (2024)
A series of different percentage of Cobalt-doped iron(III) oxide namely 1%, 3%, 5%, 7%, and 10% have been successfully synthesized using precipitation method in aqueous sloution and tested for photodegradation of methyl orange (MO) under visible light irradiation. The as-prepared photocatalysts were characterized using Ultraviolet-Visible (UV-Vis) and Fourier Transform Infrared (FTIR) spectroscopy for their band gap energy, photocatalytic activity and chemical bonding, respectively. Doping with Co enable the reduction of band gap energy of the as -prepared photocatalyst where 7% Co dopant showed the lowest value of band gap energy (2.40 eV) as compared to the pristine Fe2O3 (2.6 eV). The photodegradation of MO has reached the highest activity over 7% Co doped Fe2O3 whilst further addition of CO (10%), the degaradtion of MO remain unchanged.